Tuberculinização e aspectos epidemiológicos da tuberculose caprina na mesorregião do Triângulo Mineiro e Alto Paranaíba - Bombonato, Nadia Grandi (2009)
Data on caprine tuberculosis in Brazil and its importance for public health are scarce. Therefore, the purpose of this study was to investigate the occurrence and examine epidemiological aspects of tuberculosis in dairy goat herds in the Triângulo Mineiro and Alto Paranaíba mesoregion in the state of Minas Gerais, Brazil. Two hundred and thirty-three goats from seven dairy farms were tuberculinized using the comparative cervical tuberculin test, taking as reference the procedures and interpretation criteria of standard results for this species. Of the animals subjected to the test, 1.29% (3/233) reacted positively, 2.14% (5/233) showed inconclusive reactions, and 96.57% (225/233) showed no reaction. All the goats that tested positive and one showing an inconclusive response were necropsied. Samples of lymph nodes, liver, lung and kidney presenting alterations were collected for a histopathological examination (hematoxylin-eosin). Material removed from abscesses and lymph node fragments were cultured in Stonebrink and Petragnani culture media. An epidemiological inquiry was carried out to analyze risk factors on the farms. The necropsied animals did not exhibit macroscopic lesions suggestive of tuberculosis or any histopathological alterations, nor did the cultures show Mycobacterium sp. growth. The goats prevalence rate to tuberculin reaction was 1.29%, which may represent a zoonotic risk in this mesoregion since these are dairy herds. The interpretation of the epidemiological records, allied to the results of the tuberculinization procedure, indicated positive reagents only on a farm where fresh cow milk was fed to newborn goat kids.